Analysis of Factors That Contribute To The Effectiveness of The Program for Increasing The Role of Women Towards a Healthy and Prosperous Family - Indi Nervilia; Aswin Naldi Sahim; Nurmansyah Nurmansyah (Return : Study of Management, Economic and Bussines, 2024)
One of the efforts to strengthen the role of women in the family context to improve overall family health and welfare is the Increasing the Role of Women towards a Healthy and Prosperous Family program. After one year, an analysis was carried out to find out what factors affect the effectiveness of this program. Specifically examine the influence of participation factors in programs, education, training, access to resources, culture and norms on increasing the role of women in the family and further on family welfare. Also culture and norms as moderator variables for the influence between changes in roles in the family on family well-being. Respondents were program participants, and were immediately interviewed for filling out questionnaires, which were processed with PLS Smart4 Structural Equation Modeling (SEM) statistics. The findings of this study are that participation factors in programs, education, training, access to resources to change the role of women in the family play a role in the effectiveness of family welfare programs. Culture and norms proved to be moderator variables for the influence of changing roles in the family on family well-being. Meanwhile, culture and norms are not moderator variables for the influence of participant participation in programs and training education held on participants' access to resources. With this, it can be understood what factors need to be done to be fostered and improved, so as to accelerate the success process of the program to increase the role of women towards a healthy and prosperous family in Indonesia.